2014
DOI: 10.1016/j.jhep.2014.05.027
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase activated thymidine analogue pro-drug is a new molecule targeting hepatocellular carcinoma

Abstract: Background & AimsHepatocellular carcinoma (HCC) is one of the most common malignancies worldwide. Although hepatectomy and transplantation have significantly improved survival, there is no effective chemotherapeutic treatment for HCC and its prognosis remains poor. Sustained activation of telomerase is essential for the growth and progression of HCC, suggesting that telomerase is a rational target for HCC therapy. Therefore, we developed a thymidine analogue pro-drug, acycloguanosyl-5′-thymidyltriphosphate (AC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…HBV transgenic mouse models are widely used for study of HCC development 28 29 . A strain of HBV transgenic mouse C57BL/6J-Tg(Alb1HBV)44Bri/J is also observed the development of liver fibrosis 14 30 , which was verified in our study.…”
Section: Discussionmentioning
confidence: 99%
“…HBV transgenic mouse models are widely used for study of HCC development 28 29 . A strain of HBV transgenic mouse C57BL/6J-Tg(Alb1HBV)44Bri/J is also observed the development of liver fibrosis 14 30 , which was verified in our study.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the exact role of ALKBH5 in HCC, we measured the protein expression of ALKBH5 in four HCC cell lines (HepG2, HUH-7, Sk-hep1, and Hep3b) which often used in liver cancer study 35 , 36 . The results showed that the expression of ALKBH5 was higher in HUH-7 and Sk-hep1 cells and lower in Hep3b cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Telomerase, a prominent feature of many HCCs, can be used as a therapeutic perk to counter the proliferation of the same tumoral cell. An association with sorafenib is pictured, even if statistically significant results cannot be obtained [50] .…”
Section: Treatment Perspectivesmentioning
confidence: 97%